2020
DOI: 10.1186/s13018-020-01789-1
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin is present in synovial fluid of patients undergoing total knee arthroplasty

Abstract: Background: Osteoarthritis is a mechanical abnormality characterized by chronic joint pain associated with degeneration of the articular cartilage, synovitis, and local inflammation, leading to loss of function and pain. A connection exists between the peripheral nervous system and inflammatory joint degeneration. The process by which inflammation is influenced by the nervous system is known as neuroinflammation. One of the neuropeptides involved in peripheral neuroinflammation is nociceptin, a peptide related… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Clinical data indicated that nociceptin can be detected in human synovial fluid and plasma, with lower levels in the synovial fluid. However, only extracellular nociceptin levels were measured [ 25 ]. Another study showed that nociceptin mRNA was expressed in human peripheral mononuclear neutrophils (PMN), with nociceptin evoking PMN chemotaxis and recruitment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data indicated that nociceptin can be detected in human synovial fluid and plasma, with lower levels in the synovial fluid. However, only extracellular nociceptin levels were measured [ 25 ]. Another study showed that nociceptin mRNA was expressed in human peripheral mononuclear neutrophils (PMN), with nociceptin evoking PMN chemotaxis and recruitment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%